1999
DOI: 10.1038/sj.bjc.6690789
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ploidy, recruitment, environmental factors, and tamoxifen treatment on the expression of sigma-2 receptors in proliferating and quiescent tumour cells

Abstract: Summary Recently, we demonstrated that sigma-2 receptors may have the potential to be a biomarker of tumour cell proliferation (Mach et al (1997) Cancer Res 57: 156-161). If sigma-2 receptors were a biomarker of tumour cell proliferation, they would be amenable to detection by non-invasive imaging procedures, thus eliminating many of the problems associated with the flow cytometric measures of tumour cell proliferation presently used in the clinic. To be a good biomarker of tumour cell proliferation, the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 28 publications
2
60
0
Order By: Relevance
“…Expression of both subtypes of s-receptors in tumor cells and in solid tumors is related to cellular proliferation (3,10,11). A recent study on a large number of human cell lines showed that cancer cells express much higher levels of s 1 -receptors than do corresponding noncancerous cells (3).…”
mentioning
confidence: 99%
“…Expression of both subtypes of s-receptors in tumor cells and in solid tumors is related to cellular proliferation (3,10,11). A recent study on a large number of human cell lines showed that cancer cells express much higher levels of s 1 -receptors than do corresponding noncancerous cells (3).…”
mentioning
confidence: 99%
“…The density of σ 2 receptors in the 66P cells was found to be quite high, ~900,000 copies/cell versus ~90,000 receptors/cell in the 66Q cells. This group also reported that the expression kinetics of σ 2 receptors follows the growth kinetics of the 66 cells ( Figure 1B) [15]. A subsequent study in solid tumor xenografts of the same tumor cell lines demonstrated the identical P:Q ratio to that measured in the cell culture condition [16].…”
mentioning
confidence: 65%
“…18,23,29) As an initial screening to assess the relative potential The expression of sigma receptors in various tumors may serve as a better biomarker of a tumor's proliferative status. [14][15][16] In vitro studies of tumor cells in a proliferative state showed an 8-10 times higher sigma receptor density than tumor cells in a quiescent state. 16) Expression of the sigma receptors parallels the proliferative status of breast tumors implanted in nude mice.…”
Section: Resultsmentioning
confidence: 99%